1918
DOI: 10.1093/oxfordjournals.aob.a089689
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the Anatomy of Teratological Seedlings

Abstract: With seventeen Figures in the Text. HE discovery by one of us of a strain of wallflower which threw Jl a considerable percentage of abnormal seedlings seemed to offer a favourable opportunity for an anatomical study of specific teratological polycotyly on a somewhat more extensive scale than had hitherto been possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1928
1928
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…For example, it was found that the usually high photosynthesis rates of young cotyledons enhanced faster root growth in Douglas fir seedlings [96,97]. In contrast, polycotyly in angiosperms "has apparently been treated in the past as a rare and somewhat trivial abnormality" [4], and the literature from teratological studies, as mentioned above, has revealed that a variable proportion of angiosperm polycotyly was aborted, had abnormal growth, and/or did not bear seeds (e.g., [62,98]). Such a reduced seedling fitness could be explained if the cotyledon number is considered a fixed or threshold trait [99,100], as the trait might be largely canalized [101,102] and may have a threshold (or evolutionary constraint) buffered against a certain amount of genetic and environmental change [90].…”
Section: Evolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it was found that the usually high photosynthesis rates of young cotyledons enhanced faster root growth in Douglas fir seedlings [96,97]. In contrast, polycotyly in angiosperms "has apparently been treated in the past as a rare and somewhat trivial abnormality" [4], and the literature from teratological studies, as mentioned above, has revealed that a variable proportion of angiosperm polycotyly was aborted, had abnormal growth, and/or did not bear seeds (e.g., [62,98]). Such a reduced seedling fitness could be explained if the cotyledon number is considered a fixed or threshold trait [99,100], as the trait might be largely canalized [101,102] and may have a threshold (or evolutionary constraint) buffered against a certain amount of genetic and environmental change [90].…”
Section: Evolutionmentioning
confidence: 99%
“…A large number of anatomic studies on teratological seedlings were undertaken to elucidate obscure morphological problems for a better understanding of cotyledons’ origins (e.g., [ 5 , 11 , 12 , 13 , 18 , 21 , 61 , 62 , 63 , 64 , 65 , 66 ]). It was found that the modes of increasing or decreasing the number of cotyledons in a species could be explained by cotyledon fusion, loss, or fission [ 5 , 18 , 62 ].…”
Section: Advances In Polycotyly Researchmentioning
confidence: 99%
See 1 more Smart Citation